Poly‐ADP ribose polymerase‐14 limits severity of allergic skin disease. Issue 3 (27th July 2017) - Krishnamurthy, Purna; Da‐Silva‐Arnold, Sonia; Turner, Matthew J.; Travers, Jeffrey B.; Kaplan, Mark H.
Summary: Poly‐ADP ribose polymerase‐14 (PARP14 or ARTD8) was initially identified as a transcriptional co‐activator for signal transducer and activator of transcription 6 (Stat6), where the presence of interleukin‐4 (IL‐4) and activated Stat6 induces the enzymatic activity of PARP14 that promotes T helper type 2 differentiation and allergic airway disease. To further our understanding of PARP14 in allergic disease, we studied the function of PARP14 in allergic inflammation of skin using mice that express constitutively active Stat6 in T cells (Stat6VT) and develop spontaneous inflammation of the skin. We mated Stat6VT mice to Parp14 −/− mice and observed that approximately 75% of the Stat6VT × Parp14 −/− mice develop severe atopic dermatitis (AD)‐like lesions, compared with about 50% of Stat6VT mice, and have increased morbidity compared with Stat6VT mice. Despite this, gene expression in the skin and the cellular infiltrates was only modestly altered by the absence of PARP14. In contrast, we saw significant changes in systemic T‐cell cytokine production. Moreover, adoptive transfer experiments demonstrated that decreases in IL‐4 production reflected a cell intrinsic role for PARP14 in Th2 cytokine control. Hence, our data suggest that although PARP14 has similar effects on T‐cell cytokine production in several allergic disease models, the outcome of those effects is distinct, depending on the target organ of disease. Abstract : The atopic dermatitis‐like disease that develops in Stat6VT mice is exacerbated by deficiency in PARP14.